Influence of Individual Cognition, Satisfaction, and the Theory of Planned Behavior on Tenant Loyalty - Lee, Chun-chang; Yeh, Wen-chih; Chang, Hung-chung; Yu, Zheng; Tsai, Zheng-yang (Frontiers in Psychology, 2022)
This study proposed a conceptual framework and explored the influence of personal-level variables such as cognition, affection, conation, and attitude, as well as the theory of planned behavior, on tenant loyalty using situational influence as a moderator variable. Structural equation modeling was employed for parameter estimation. A total of 315 questionnaires were administered to housing tenants residing in Kaohsiung City, of which 300 were recovered, a recovery rate of 95.2%. The results are as follows: Tenants’ cognition and conation positively influenced their attitude toward their tenancy; tenants’ attitude significantly and positively influenced their satisfaction and loyalty; tenant satisfaction significantly and positively influenced tenant loyalty; perceived behavioral control significantly and positively influenced tenant loyalty; and subjective norms significantly and positively influenced tenant loyalty. Regarding the influence of attitude on tenant loyalty, the inclusion of a situational influence-based moderator variable—i.e., whether a tenant has friends or relatives living nearby —revealed that the presence of this variable significantly diminishes the influence of attitude on loyalty. The findings indicate that landlords could improve the quality of their services by implementing sustainable management measures to strengthen tenant satisfaction and, consequently, tenant loyalty.